2000
DOI: 10.1128/aac.44.9.2475-2484.2000
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Mutations Selected in Patients Failing Efavirenz Combination Therapy

Abstract: Efavirenz is a potent and selective nonnucleoside inhibitor of human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT). Nucleotide sequence analyses of the protease and RT genes (coding region for amino acids 1 to 229) of multiple cloned HIV-1 genomes from virus found in the plasma of patients in phase II clinical studies of efavirenz combination therapy were undertaken in order to identify the spectrum of mutations in plasma-borne HIV-1 associated with virological treatment failure. A K103N sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
207
2
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(228 citation statements)
references
References 33 publications
16
207
2
3
Order By: Relevance
“…There did appear to be some differences in the relative prevalence of other NNRTI-resistance mutations in this trial, compared to the earlier trials in which EFV was given either in combination with IDV or zidovudine and lamivudine 32,33 . In those earlier trials, the accumulation of V108I or P225H occurred commonly after the emergence of K103N, with K103N+L100I or G190S/A occurring uncommonly.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…There did appear to be some differences in the relative prevalence of other NNRTI-resistance mutations in this trial, compared to the earlier trials in which EFV was given either in combination with IDV or zidovudine and lamivudine 32,33 . In those earlier trials, the accumulation of V108I or P225H occurred commonly after the emergence of K103N, with K103N+L100I or G190S/A occurring uncommonly.…”
Section: Discussionmentioning
confidence: 85%
“…L100I and mutations at codon 190 have been less commonly observed than K103N with either V108I or P225H in prior published studies of EFV treatment 32,33 . We therefore evaluated whether there were factors that favored the development of these normally less common EFV resistance mutations.…”
Section: Resistance Patterns At Failurementioning
confidence: 99%
“…The most commonly seen resistance mutations in clinical isolates from patients failing nevirapine and delavirdine therapy are K103N and Y181C; K103N is most common during efavirenz failure (9,43,145). However, several mutations, such as G190S, P236L, and V106A, are equally resistant to one or more of these drugs but occur uncommonly in clinical isolates.…”
Section: Mutations Conferring Resistance To Reversementioning
confidence: 99%
“…One of the major concerns for patients who receive an NNRTI as part of their antiretroviral regimen is the development of resistant viruses, which requires only a single point mutation to confer high-level, cross-class resistance among NNRTIs [55]. The impact of the CYP2B6 genotype on the development of NNRTI resistant virus is currently unknown; however, Ribaudo et al [19] demonstrated that CYP2B6-G516T genotypes, which were associated with plasma EFV levels, predicted the duration of plasma EFV levels exceeding 95% inhibitory concentration.…”
Section: Impact Of Cyp2b6 Genotype On the Development Of Nnrti Resistmentioning
confidence: 99%